KARAKTERISTIK KIMIA DAN MIKROBIOLOGI SILASE KEONG MAS (Pomacea canaliculata) DENGAN PENAMBAHAN ASAM FORMAT DAN BAKTERI ASAM LAKTAT 3B104 - Yovitaro Noviana N; Susi Lestari; Siti Hanggita R.J. (Universitas Sriwijaya, 2012)
The purposes of this research were to know characteristics of golden snail (Pomacea canaliculata) silage processed chemically and microbiologycal using lactid acid bacteria culture (LAB) 3B104. The research used the Factorial Randomized Block Designed with two factors of treatment and each was replicated three times. The factors were different of percentation formic acid (formic acid 2.5%, 3.0% and 3.5%), without and given lactid acid bacteria (LAB) culture 3B104. The parameters were chemical analysis (pH value, moisture content, ash content, protein content, fat content, carbohydrate, crude fiber) and microbiologycal analysis (Total Plate Count, Salmonella test, Escherischia coli test). The result of this research were different ration of percentage formic acid, without and given lactid acid bacteria culture (LAB) 3B104 had significant effect on pH value, moisture content, protein content, carbohydrate and crude fiber. The average value were pH value after fermentation (4.73-5.46), moisture content (77.98%-81.59%), ash content (2.25%-3.97%), protein content (10.88%-14.54%), fat content (0.45%-0.68%.), carbohydrate content (2.00%-3.70%.), crude fiber (0.56%-1.47%). The highest protein content (14.54%) was found in the treatment of formic acid 3.5% without given lactid acid bacteria culture (LAB) 3B104. The microbiologycal analysis showed total plate count (5.78 log CFU/gr-7.29 log CFU/gr), negative Salmonella and Escherischia coli. Â Keyword: golden snail silage, formic acid, lactid acid bacteria (LAB)